Legislation on Food Waste Prevention: Overview of Practices in Industrialized Countries - Tokareva, Tatjana; Eglīte, Aija (Socialiniai tyrimai, 2015)
The world is producing enough food to feed the world’s entire population. Yet almost one billion people go hungry. Another billion are malnourished, lacking the essential micronutrients they need to lead healthy lives. One billion adults are overweight of which almost half a billion are obese, and can easily waste the food they have. But even if the amounts of wasted food are significant, most industrialized countries are only at the beginning on the road to food waste reduction. Since in some countries, glass, paper or cardboard recycling is not well established, it is another level of confusion how to get people think about waste sorting or organic waste. This paper aims at identifying how differently industrialized countries deal with food waste and analyze which method is more successful when it comes to food waste reduction.
Keywords: recycling; food donation; legislation; waste; landfill; Japan; US; EU